HUBUNGAN POLIGAMI DAN KESETARAAN GENDER DALAM PRESPEKTIF HUKUM ISLAM - Septiya Dewi Andini; Fathurrahman Alfa; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
This study aims to describe the relationship between polygamy and gender equality in the perspective of Islamic law. Research using this literature review shows that in the perspective of Islamic law Polygamy is permissible with strict terms and conditions that polygamy is limited to four wives, and the main condition is that it must be fair. In Surah An-Nisa' verse 3, it is explained that if you are afraid of not being able to do justice, then marry only one person, then in Islamic law based on the Qur'an and Hadith polygamy is not a recommendation, but an option When in a state of absolute urgency to resolve the case. which cannot be solved in any other way. Or in other words that polygamy is permitted by Islam and is not prohibited unless it is feared that the good will be defeated by the bad. Nowadays, the problem of polygamy is often debated, especially for feminists, that polygamy in this century is carried out based on women only to satisfy men's desires and this is a form of gender inequality. Meanwhile, explained in (QS. At-Taubah 9:71) is an explanation of gender equality which is the procedure for how men and women live on earth where each other is obliged to uphold good deeds and good deeds, namely by helping each other. , compassion and respect for human rights as human beings and also as servants, regardless of gender quality.